Identifikasi Jenis Bangunan di Daerah Bahaya Longsor di Desa Candikuning - Adelia Novita Marampa; Ni Made Trigunasih; Putu Perdana Kusuma Wiguna (Nandur, 2024)
This research aims to identify building types in landslide hazard areas and to determine the distribution of buildings in landslide hazard areas in Candikuning Village. The method used is detailed survey per building by assessing buildings in landslide hazard area by direct field survey. Field results show that building types in the hazard area are divided into 3 classes, namely high hazard class, medium hazard class, and low hazard class with 7 building categories consisting of tourism buildings, residential buildings, agricultural buildings, worship facilities, government buildings, and educational facilities. There are 8 buildings in the high hazard class area, where there are 7 residential buildings and 1 trade and service building. There are 584 buildings in the medium hazard class area consisting of 87 tourism buildings, 432 residential buildings, 51 trade and service buildings, 6 agricultural buildings, 4 worship facilities, 3 government facilities and 11 educational facilities. The total number of low hazard class is 1624 buildings which are divided into 180 tourism buildings, 1137 residential buildings, 153 trade and service buildings, 25 agricultural buildings, 23 government buildings and 22 educational facilities buildings. Tourism and residential buildings are in the high hazard class. Raising public awareness is essential in terms of building site selection. This can be achieved through selecting building sites away from steep slopes and proper land use by not planting annuals on slopes.